Effectiveness and Optical Quality of Topical 3.0% Diquafosol versus 0.05% Cyclosporine A in Dry Eye Patients following Cataract Surgery - Jang Hoon Lee; In Seok Song; Kyoung Lae Kim; Sam Young Yoon (Journal of Ophthalmology)
Purpose. To evaluate the effectiveness and optical quality of 3.0% topical diquafosol versus 0.05% cyclosporine A in dry eye patients following cataract surgery. Methods. In total, 40 eyes of 40 patients newly diagnosed with dry eye syndrome 1 week after cataract surgery were randomized to receive either 3.0% diquafosol ophthalmic solution six times daily or 0.05% cyclosporine A twice daily for 3 months. Outcome measures were tear film break-up time (TBUT), results on Schirmer 1 test, ocular surface staining score, the ocular surface disease index (OSDI) score, and higher-order aberrations (HOAs). Measurements were taken at baseline and at 1, 2, and 3 months. Results. In the diquafosol group, TBUT showed higher outcomes than the cyclosporine A group at 1 and 3 months. Both groups showed increased scores on Schirmer 1 test. The ocular surface staining score decreased in all periods in both groups. Vertical coma and total HOAs decreased more in the cyclosporine A group than in the diquafosol group at 3 months. Conclusion. Both 3.0% diquafosol and 0.05% cyclosporine A were effective in treating dry eye after cataract surgery. Diquafosol was more effective in increasing the tear secretion, but cyclosporine A was more effective in improving optical aberrations.